Occurrence of Pesticide Residues in Cooked Chicken Meat Products - kumar, M.Muthu; Vaithiyanathan, S.; Naveena, B.M.; Sen, A.R.; Kulkarni, V.V. (Journal of Meat Science, 2015)
A study was conducted to estimate the levels of various organochlorine pesticide residues in cooked chicken meat products. Wet cooked (Kadai Chicken), deep fat fried (Chicken 65) and dry cooked (Tandori chicken) chicken meat products (each 14 samples) were collected from restaurants in Hyderabad and analysed for the presence of pesticide residues using gas chromatograph equipped with an electron capture detector. Overall, 42.86 % of cooked meat products samples were showed presence of pesticide residues. Among the analysed samples, chicken 65 (57.14 %) and tandoori chicken (50.0 %) showed higher incidence of contamination. Among the pesticides, residues of aldrin (26.19%) were more frequently observed. The kadai chicken had residues of γ HCH, δ HCH and dieldrin with a concentration (ppm) of 0.011, 0.033 and 0.026, respectively. Residues of δ HCH, aldrin, dieldrin and endosulfan were observed in chicken 65. The tandoori chicken showed residues of α HCH, δ HCH, aldrin, dieldrin and endosulfan with a concentration (ppm) of 0.047, 0.010, 0.058, 0.050 and 0.012, respectively. However, the levels of pesticide residues recorded in the study were lower than the maximum residue limit stipulated by Food Safety Standards Regulations (Contaminants, toxins and Residues) 2011.
Keywords: Pesticide residues; Cooked chicken meat products